Predictors of Tobacco Smoking in Male Adolescents in Hamadan Based on the Theory of Planned Behavior - Majid Barati; Shamsodin Niknami; Alireza Hidarnia*; Hamid Allahverdipour (Hamadan University of Medical Sciences, 2014)
Background and Objectives: The cognitive determinants of social behaviors play an important role in adolescents' decision-making for starting smoking. The present study was therefore conducted to determine the predictors of tobacco smoking in male adolescents in Hamadan, Iran, based on the Theory of Planned Behavior (TPB). Materials and Methods: The present descriptive-analytical study was conducted on 810 male high school students in Hamadan selected through the multistage sampling method. Data were collected using a self-report questionnaire with a section on participants' demographic information and another section based on the TPB constructs. Data were then analyzed in SPSS-18 and AMOS-18 using the Pearson correlation test and the indices of model fit. Results: Overall, 17.2% of the male adolescents reported to have smoked cigarettes in the past. Perceived behavioral control, subjective norms and attitude were the best predictors of behavioral intention for tobacco smoking, in the order of importance (P<0.001). Perceived behavioral control (&beta=-0.59 P<0.001) was a better predictor of the studied behavior than behavioral intention (&beta=0.11 P<0.001). In the structural equation model, TPB constructs accounted for 32% of behavioral intention variances and 50% of behavior variances. Conclusion: The results demonstrated the poor role of behavioral intention in reporting smoking behaviors in male adolescents. Other psychological factors that affect adolescents' decision-making regarding tobacco smoking should also be scrutinized.